2020
DOI: 10.1108/apjml-02-2020-0085
|View full text |Cite
|
Sign up to set email alerts
|

Trust transfer and the intention to use app-enabled carpooling service

Abstract: PurposeIn China, with the rapid dissemination of mobile communications technology along with congested traffic and increasingly expensive transportation costs, consumers are turning to smartphone-enabled, ride-sharing services. Sharing economy requires trust in strangers. Based on trust transfer theory and a dyadic conceptualization of trust from cognitive to affective, the purpose of this study is to examine trust building through the use of Didi, a third-party, ride-sharing platform that mediates exchanges a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…Our results support previous research and confirm that carpooling is strongly determined by individuals’ trust level ( Wu and Neill, 2020 ). Indeed, our results, in line with Tsai et al (2021) highlight a direct effect from trust on the intention to carpool.…”
Section: Discussionsupporting
confidence: 92%
“…Our results support previous research and confirm that carpooling is strongly determined by individuals’ trust level ( Wu and Neill, 2020 ). Indeed, our results, in line with Tsai et al (2021) highlight a direct effect from trust on the intention to carpool.…”
Section: Discussionsupporting
confidence: 92%
“… Shao et al (2020) indicated that government support and platform reputation are the main factors that affect consumers’ intention to continue to use ride-sharing services. Wu and Neill (2021) verified that platforms affect consumers’ trust and then affect their intention to adopt ride-sharing services. Lee and Cha (2022) confirmed that anti-consumption affects the formation of consumers’ trust in the ride-sharing service.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 93%
“…On the other side, lack of trust is a major barrier for carpooling, especially for women. People are more likely to carpool either within closed carpooling schemes, such as within organizations [34], or within platforms with a reputation-based scheme that help increase trust [38,39].…”
Section: Literature Collection #1mentioning
confidence: 99%